Formulating problems for commercializing new technologies: The case of environmental innovation. Issue 1 (March 2015) - Björkdahl, Joakim; Linder, Marcus
Summary Prior research on environmental innovation has highlighted the importance for the firm of a shared environmental vision but has not empirically explored why or what are its effects. The purpose of this paper is to analyze the effect of an environmental sustainability vision for the development and commercialization of environmental innovations. We conduct an in-depth, multilevel investigation of the development of green product lines in a multinational manufacturing firm, based primarily on interview data collected over five years. By analyzing the interaction between environmental vision and the product development process as an interaction between problem formulation and the search for problem solutions, we explain how and why a shared environmental vision can accelerate environmental innovation. Specifically, we show that a shared environmental vision can lead to an increase in the number of application areas, and increased sales of previously customized solutions but that the efficacy of the shared vision is dependent on a good match between the environmental problems being focused on, and the core competencies of the firm.